Activated charcoal and gastric absorption of iron compounds. Issue 1 (1st January 2002) - Jones, Steve; Ali, Baha
Abstract : A short cut review was carried out to establish whether activated charcoal is effective in iron overdose. Altogether 17 papers were found using the reported search, of which only one was relevant. The author, date and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of this paper are shown in table 4. A clinical bottom line is stated.